Packed bed and flow method using same
A packed layer composed of porous particles and fine powders with controlled sizes addresses the flow and pressure loss issues in packed columns, maintaining catalytic activity without the need for adhesives.
Patent Information
- Application Number
- JP2019239305
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2019-12-27
- Publication Date
- 2025-04-14
- Estimated Expiration
- 2039-12-27
AI Technical Summary
In flow methods using packed columns, fine powder catalyst particles are not effectively fixed, leading to flow issues, pressure loss, and reduced catalytic activity due to the lack of an adhesive and uneven distribution within the reaction tube.
A packed layer formed from a mixture of porous particles with controlled through-hole sizes and fine powders with specific primary particle diameters, which suppresses the flow of fine powders without using an adhesive and maintains catalytic activity.
The solution effectively reduces pressure loss and maintains catalytic activity by ensuring the fine powders are dispersed within the porous particles, preventing flow and clogging issues.
Smart Images

Figure 0007660869000021 
Figure 0007660869000022 
Figure 0007660869000023
Abstract
Description
[Technical field]
[0001] The present invention relates to a packed bed and a flow method using the same. [Background technology]
[0002] As material functions such as catalytic reactions become more sophisticated, nanomaterials such as gold nanoparticle catalysts, metal organic frameworks (MOFs), and graphene oxide, as well as nanoparticles carrying peptides, proteins, enzymes, etc., have been developed.
[0003] Nanomaterials are often actually provided in the form of fine powder, and it is believed that nanometer-sized primary particles form micrometer-sized secondary particles through aggregation or other processes.
[0004] When nanomaterials are used in catalytic reactions, etc., there is a method in which fine powders as catalyst particles are dispersed in a liquid or gas to carry out the reaction. For example, there is a method in which two types of fine powders as catalyst particles are dispersed in a liquid, stirred, and optically resolved as a batch method (Non-Patent Document 1, Non-Patent Document 2, etc.).
[0005] Furthermore, when nanomaterials are used in a flow-type flow catalytic reaction, fine powders as catalyst particles are filled into a reaction tube, and a reaction fluid such as water or gas is passed through the reaction tube. However, when the reaction tube is filled with fine powders as catalyst particles, the passage of the reaction fluid is narrowed, resulting in a large pressure loss (hereinafter also referred to as "pressure loss"). Therefore, it becomes difficult to pass a sufficient flow rate of the reaction fluid through the reaction tube.
[0006] Conventionally, as a method for reducing pressure loss, a method is known in which a reaction tube filled with fine powder as catalyst particles is mixed with quartz sand as a gap filler for the fine powder, and a reaction fluid is passed through the reaction tube (Non-Patent Document 3, Non-Patent Document 4, etc.). In addition, a method is known in which catalyst particles are supported on a monolith having a hierarchical porous structure with low pressure loss (Non-Patent Document 5). Furthermore, a method is known in which fine powder as catalyst particles is supported on macroporous particles having macropores in the micron range (Patent Document 1). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Special Publication No. 2006-506224 [Non-patent literature]
[0008] [Non-Patent Document 1] Shinji Kawanishi, Shinya Oki, Dhiman Kundu, and Shuji Akai, “Lipase / Oxovanadium Co-Catalyzed Dynamic Kinetic Resolution of Propargyl Alcohols: Competition between Racialization and Rearrangement”, Org. Lett. 2019, 21, pp 2978-2982. [Non-Patent Document 2] Koji Sugiyama, Yasuhiro Oki, Shinji Kawanishi, Katsuya Kato, Takashi Ikawa, Masahiro Egi and Shuji Akai, “Spatial effects of oxovanadium-immobilized mesoporous silica on racemization of alcohols and application in lipase-catalyzed dynamic kinetic resolution”, Catal. Sci. Technol., 2016, 6, pp. 101-1 5023-5
Outdoor Tools3
Outdoor Tools 4
Direct Environment 5
[0009] However, in the flow method using a packed column in which fine powder as catalyst particles and gap filler are uniformly mixed, the catalyst particles made of fine powder are not fixed to the gap filler, and when a fluid (liquid, gas, etc.) is passed through, the fine powder as catalyst particles flows with the fluid and flows out from the column outlet. Therefore, it is difficult to uniformly fill the reaction tube with the mixture of the catalyst particles made of fine powder and the gap filler, and there is a problem that the catalytic activity is not exerted.
[0010] In addition, the outflowing fine powder becomes concentrated at the outlet of the packed column and causes clogging, resulting in an increase in pressure, which causes a problem in that the effect of reducing pressure loss cannot be fully exerted.
[0011] Furthermore, when an organic polymer, an inorganic binder, or the like is used as an adhesive to fix the fine powder as the catalyst particles to the gap filling material, the surface of the fine powder as the catalyst particles becomes buried in the adhesive, resulting in a problem that the catalytic activity is not exerted.
[0012] The present invention has been made in view of the above circumstances. That is, an object of the present invention is to provide a packed bed capable of suppressing the outflow of fine powder without using an adhesive and maintaining catalytic activity, and a flow method using the same. [Means for solving the problem]
[0013] As a result of intensive research into achieving the above-mentioned object, the inventors have found that the above-mentioned object can be achieved by using a packed bed formed by filling a mixture of porous particles having through holes, and in which the size and particle size of the through holes are controlled within an appropriate range, and a fine powder in which the average primary particle diameter is controlled within an appropriate range, and have thus completed the present invention.
[0014] The present invention provides the inventions described in the following sections. Section 1. A packed bed formed of a mixture of porous particles and fine powder, (1) The porous particle has a skeleton, the skeleton has through holes, the through holes have a diameter of 0.1 to 100 μm, the through holes have a most frequent pore size of a pore size distribution of 0.5 μm or more and 50 μm or less, and the porous particle has a particle size of 20 μm or more and 3000 μm or less, (2) the average primary particle size of the fine powder is 1 nm or more and is 80% or less of the most frequent pore size in the pore size distribution of the through holes; (3) The bulk density of the porous particles is 0.05 to 7.5 (mg / mm 3 ), A packed bed characterized by: term 2 . The bulk density of the fine powder is 0.02 to 7.5 (mg / mm 3 ), the term 1 to The filling layer described. term 3 . The bulk density of the packed bed is 0.05 to 7.5 (mg / mm 3 ), term 1 or 2 The filling layer according to claim 1. term 4 . Item 1~ 3 The filling bed according to any one of claims 1 to 5, A packed bed, in which a mixing ratio of the porous particles and the fine powder in the packed bed changes stepwise. term 5 . The mixture further contains enzyme particles. 4 The filling layer according to any one of claims 1 to 5. term 6 . The enzyme particles are lipase. 5 The filling layer according to claim 1. term 7 . term 5 or 6 The filling layer according to claim 1, A packed bed, in which a mixing ratio of the fine powder and the enzyme particles in the packed bed changes stepwise. term 8 . Item 1~ 7 A method for passing a gas or liquid through a pipe provided with the packed bed according to any one of claims 1 to 5. Effect of the Invention
[0015] The packed bed of the present invention is formed from a mixture of porous particles having through holes, with the size and particle size of the through holes being controlled within an appropriate range, and fine powder having an average primary particle diameter controlled within an appropriate range. Therefore, the outflow of the fine powder can be suppressed without using an adhesive, and catalytic activity can be maintained. [Brief description of the drawings]
[0016] [Figure 1] 1(a) is a scanning electron microscope (SEM) photograph of particle 2 obtained in Example 1. 1(b) is a graph showing the through hole diameter distribution of particle 2 obtained in Example 1, in which the horizontal axis indicates the through hole diameter (μm) and the vertical axis indicates the frequency (number) of the analyzed through holes. [Diagram 2] 1 is a graph showing the pore size distribution of particles 2 obtained in Example 1, in which the horizontal axis represents pore size (nm) and the vertical axis represents log differential pore volume (cm3 / g). [Diagram 3] 1(a) is an SEM photograph of particle 2 obtained in Example 3. FIG. 1(b) is a through-hole size distribution graph of particle 2 obtained in Example 3, in which the horizontal axis indicates the through-hole size (μm) and the vertical axis indicates the frequency (number) of the analyzed through-holes. [Figure 4] 1 is a graph showing the measurement results of pressure loss when He gas was passed through the quartz tubes equipped with packed layers obtained in Examples 1 and 2 and Comparative Examples 1 to 3. The horizontal axis shows the He gas flow rate (mL / min), and the vertical axis shows the pressure loss (kPa). [Diagram 5] 1 is a graph showing the measurement results of pressure loss when He gas was passed through the quartz tubes equipped with the packed bed obtained in Example 3 and Comparative Example 4. The horizontal axis shows the He gas flow rate (mL / min), and the vertical axis shows the pressure loss (kPa). [Figure 6] FIG. 2 is a diagram showing a first region, a second region, and a third region in the catalytic reaction columns equipped with the packed beds obtained in Examples 15 to 24. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] In this specification, a numerical range indicated using "~" indicates a range that includes the numerical values before and after "~" as the minimum and maximum values, respectively.
[0018] In this specification, the term "through hole" is also called a macro hole or macropore, and is of submicron to micron size, typically a hole with a diameter of 0.1 to 100 μm.
[0019] In this specification, the term "pore" is also called mesopore, and refers to a hole that typically has a diameter of 1 to 200 nm and is smaller than a through-hole.
[0020] In this specification, the terms "integral porous body" and "monolith-type porous body" are used interchangeably and refer to a porous body having a characteristic structure in which one of the three sides of the structure is 1 mm or more long and a mesh-like skeleton on the order of micrometers is connected. The etymology of the term means a single piece of stone, and it looks like a single piece of chalk, and when observed under an electron microscope, it has a structure in which a jungle gym-like skeleton is connected. There are countless micron-scale pores called through holes that surround the gaps in the skeleton, and there may also be nano-scale pores in the skeleton. The through holes and pores are connected without being blocked, and it is said to boast a high porosity, with pores typically accounting for about 85% of the total volume. Due to the presence of nano-scale pores, the porous body has a high specific surface area.
[0021] The porous particles used in the present invention are crushed particles obtained by crushing and classifying a monolithic porous body, and have a high porosity and specific surface area.
[0022] In this specification, the "surface of the skeleton" refers to the surface of the skeleton exposed toward the through-holes. When a porous particle has a plurality of pores in addition to the through-holes, the "surface of the skeleton" refers to the surface of the skeleton exposed toward the through-holes, and does not include the inner wall surfaces of the pores. When a porous particle has a plurality of pores in addition to the through-holes, the total surface of the skeleton, which is the combination of the "surface of the skeleton" and the inner wall surfaces of the pores, means the "surface of the porous particle".
[0023] In this specification, Me in the structural formulas means a methyl group, and Ac means an acetyl group.
[0024] The present invention includes the following embodiments. Preferred embodiments of the present invention will be described in detail below. The following description of the components may be based on representative embodiments and specific examples, but the present invention is not limited to such embodiments.
[0025] 1. packed bed The present invention relates to a packed bed formed of a mixture of porous particles and fine powder. That is, the present invention relates to a packed bed packed with a mixture of porous particles and fine powder. The packed bed of the present invention may be simply referred to as "the present invention".
[0026] In the present invention, (1) the porous particle has a skeleton, the skeleton has through holes, the through holes have a most frequent pore size in the pore size distribution of 0.1 μm to 100 μm, and the porous particle has a particle size of 20 μm to 3000 μm. That is, in the present invention, (1) the porous particle has a skeleton having through holes, the through holes have a most frequent pore size in the pore size distribution of 0.1 μm to 100 μm, and the porous particle has a particle size of 20 μm to 3000 μm.
[0027] In the present invention, (2) the average primary particle size of the fine powder is 1 nm or more, and the average primary particle size of the fine powder is 80% or less of the most frequent pore size in the pore size distribution of the through holes.
[0028] Since the present invention satisfies the above-mentioned requirements, the fine powder is dispersed inside the porous particles through the through holes, and the adhesion of the fine powder to the porous particles is increased, so that it is possible to prevent the fine powder from flowing out of the packed bed without using an adhesive.
[0029] In the present invention, since the average primary particle diameter of the fine powder is 1 nm or more and is 80% or less of the most frequent pore diameter in the pore diameter distribution of the through holes of the porous particles, it is believed that the fine powder can enter the through holes of the porous particles.
[0030] The present invention also includes an embodiment in which the aggregates of the fine powder form coarse particles, and the coarse particles are caught in the gaps between the projections and recesses of the through-holes of the porous particles. In this case, it is believed that electrostatic forces act between the gaps between the projections and recesses of the through-holes of the porous particles and the coarse particles, so that the coarse particles, which are larger than the through-holes of the porous particles, do not flow out of the packed bed.
[0031] The present invention relates to a packed bed formed of a mixture of porous particles and fine powder, (1) The porous particle has a skeleton, through holes formed in gaps in the skeleton, and a plurality of pores extending from the surface of the skeleton toward the inside, the most frequent pore size in the pore size distribution of the through holes is 0.1 μm or more and 100 μm or less, and the particle size of the porous particles is 20 μm or more and 3000 μm or less, the most frequent pore size in the pore size distribution of the pores is 1 nm or more and 200 nm or less, and is 20% or less of the most frequent pore size in the pore size distribution of the through holes; (2) It is preferable that the average primary particle diameter of the fine powder is 1 nm or more and is 80% or less of the most frequent pore diameter in the pore diameter distribution of the through holes of the porous particles.
[0032] By satisfying the above-mentioned requirements, the present invention can suppress the outflow of fine powder, maintain catalytic activity, and achieve an excellent effect of reducing pressure drop. In addition, the excellent effect of reducing pressure drop can be achieved because the packing of fine powder in the vicinity of the porous particles is disturbed, and therefore the fluid can flow effectively in the through holes without clogging the through holes with fine powder.
[0033] In the present invention, the most frequent pore size (μm) of the pore size distribution of the through holes of the porous particles is 0.1 μm or more and 100 μm or less. If the most frequent pore size of the pore size distribution of the through holes is less than 0.1 μm, when the fine powder diffuses into the through holes, the fine powder aggregates at the inlet of the through holes due to the strengthened electrostatic interaction between the through hole surface and the fine powder, causing clogging. Therefore, the fluid does not flow into the through holes, and the pressure loss cannot be reduced, which is not practical. If the most frequent pore size of the pore size distribution of the through holes exceeds 100 μm, the production of the porous particles itself is difficult.
[0034] The mode pore size (μm) of the pore size distribution of the through holes of the porous particles is preferably from 0.5 μm to 50 μm, more preferably from 0.75 μm to 20 μm, and even more preferably from 1 μm to 10 μm.
[0035] The mode pore size (nm) of the pore size distribution of the porous particles is preferably 1 nm or more and 200 nm or less, more preferably 1.5 nm or more and 150 nm or less, further preferably 2 nm or more and 100 nm or less, and particularly preferably 5 nm or more and 20 nm or less.
[0036] The most frequent pore size (nm) of the pore size distribution of the pores in the porous particle is preferably 20% or less, more preferably 15% or less, and even more preferably 10% or less of the most frequent pore size (μm) of the through-holes in the porous particle.
[0037] The most frequent pore size (nm) of the pore size distribution of the pores in the porous particle is preferably 0.01% or more, more preferably 0.05% or more, and even more preferably 0.1% or more of the most frequent pore size (μm) of the through-holes in the porous particle.
[0038] The most frequent pore size (nm) of the pore size distribution of the pores of the porous particles is preferably 1.5 nm to 150 nm, and more preferably 0.01% to 15% of the most frequent pore size (μm) of the through-holes of the porous particles. The most frequent pore size (nm) of the pore size distribution of the pores of the porous particles is more preferably 2 nm to 100 nm, and more preferably 0.05% to 10% of the most frequent pore size (μm) of the through-holes of the porous particles. The most frequent pore size (nm) of the pore size distribution of the pores of the porous particles is particularly preferably 5 nm to 20 nm, and more preferably 0.1% to 5% of the most frequent pore size (μm) of the through-holes of the porous particles.
[0039] (Method of creating a pore size distribution of through holes in porous particles) In the present invention, the most frequent pore size in the pore size distribution of the through holes in the porous particles means the mode value of the pore size distribution of the through holes observed by SEM. Specifically, the most frequent pore size distribution of the through holes observed by SEM is calculated according to the following procedure. First, the surface of the porous particles is photographed so that 20 or more through holes are displayed in the image. From the SEM photograph of the photographed porous particles, the circle equivalent diameters of 20 through holes are measured, and the integer value rounded off is taken as the through hole diameter. Then, a through hole diameter-number graph is created, and the diameter of the through hole with the largest number is taken as the most frequent pore diameter. Note that, since the overall through hole diameter distribution is constant, the calculation is performed under the assumption that the diameter of the through holes continuous within one porous particle is uniform throughout, including other particles.
[0040] In the present invention, the most frequent pore size in the pore size distribution of the porous particles means the most frequent value (mode value) of the pore size distribution calculated by the BJH method using the adsorption isotherm by the nitrogen adsorption method. Specifically, the pore size distribution of the porous particles of the present invention was analyzed by the BJH method by nitrogen adsorption measurement using a nitrogen adsorption / desorption device. The BJH method is a calculation method generally used for pore analysis, and was proposed by Barrett, Joyner, Halenda, et al. (EP Barrett, LG Joyner and P. Halenda: J. Am. Chem. Soc., 73, 373 (1951)). As a specific measurement method, the porous particles are sealed in a glass tube of a constant size, and after reducing the pressure under vacuum, the tube is cooled to the liquid nitrogen temperature, and nitrogen gas is introduced little by little while the pressure in the glass tube containing the sample is measured. This cycle is repeated to adsorb the nitrogen gas to the sample until the pressure reaches normal pressure. Next, the pressure inside the glass tube is gradually reduced, and the amount of nitrogen gas desorbed from the sample and the pressure inside the glass tube are measured, and this cycle is repeated until the relative pressure reaches 0.3 atm. The resulting amounts of adsorbed and desorbed nitrogen gas, as well as the adsorption and desorption isotherms versus relative pressure, are then measured, and the pore size distribution of the pores in the porous particles is calculated using the BJH method, assuming that the pores are cylindrical models.
[0041] In the present invention, the porous particles are prepared by pulverizing and granulating a monolithic porous body having through-holes synthesized by a sol-gel method described in detail below. Since the particle sizes of the porous particles immediately after pulverization are a mixture of large and small, the particles are classified by sieving to obtain porous particles in the desired particle size range.
[0042] Next, a method for producing porous particles will be described. The method for producing porous particles is roughly classified into a synthesis step of a monolithic porous body that is the raw material for the porous particles, and a subsequent granulation step. Examples of the monolithic porous body include a monolithic inorganic porous body made of silica gel or silica glass having through holes.
[0043] First, a synthesis process of a monolithic porous body made of silica gel or silica glass having through-holes by a sol-gel method will be described. The synthesis process is further divided into a sol preparation process, a gelation process, and a removal process.
[0044] In the sol preparation process, a silica precursor, which is the raw material for silica gel or silica glass, and a coexisting substance that acts to induce sol-gel transition and phase separation in parallel are added to an acidic or alkaline aqueous solution, and the mixture is stirred at a low temperature, for example, below 5°C, at which the sol-gel transition is unlikely to proceed, to cause a hydrolysis reaction and prepare a uniform precursor sol.
[0045] As the main component of the silica precursor, water glass (aqueous sodium silicate solution) or an inorganic or organic silane compound can be used. An example of the inorganic silane compound is a tetraalkoxysilane compound such as tetramethoxysilane, tetraethoxysilane, tetra-isopropoxysilane, tetra-n-butoxysilane, or tetra-t-butoxysilane. An example of the organic silane compound is a trialkoxysilane compound such as trimethoxysilane, triethoxysilane, triisopropoxysilane, or triphenoxysilane having a substituent such as methyl, ethyl, propyl, butyl, hexyl, octyl, decyl, hexadecyl, octadecyl, dodecyl, phenyl, vinyl, hydroxyl, ether, epoxy, aldehyde, carboxyl, ester, thionyl, thio, or amino; a dialkoxysilane compound such as methyldiethoxysilane, methyldimethoxysilane, ethyldiethoxysilane, or ethyldimethoxysilane; or a monoalkoxysilane compound such as dimethylethoxysilane or dimethylmethoxysilane. In addition, alkoxysilicates containing crosslinking reaction rate control group substitutes such as monoalkyl, dialkyl, and phenyltriethoxy, as well as oligomers such as disilane, which is a dimer, and trisilane, which is a trimer, are also expected as silica precursors. Various compounds of the above-mentioned hydrolyzable silanes are commercially available, making them easy and inexpensive to obtain, and it is also easy to control the sol-gel reaction that forms a three-dimensional crosslinked body consisting of silicon-oxygen bonds.
[0046] The acid or alkaline aqueous solution is an aqueous solution in which an acid or base that functions as a catalyst for promoting the hydrolysis reaction of the silica precursor is dissolved in a solvent. As the solvent, water; alcohols such as methanol and ethanol can be used, and water is preferably used. Specific examples of the acid include acetic acid, hydrochloric acid, sulfuric acid, nitric acid, formic acid, oxalic acid, and citric acid. Specific examples of the base include amines such as sodium hydroxide, potassium hydroxide, ammonia water, sodium carbonate, sodium hydrogen carbonate, and trimethylammonium; ammonium hydroxides such as tert-butylammonium hydroxide; and alkali metal alkoxides such as sodium methoxide.
[0047] Specific examples of the above-mentioned coexisting substances include block copolymers such as polyethylene oxide, polypropylene oxide, polyacrylic acid, and polyethylene oxide-polypropylene oxide block copolymers; cationic surfactants such as cetyltrimethylammonium chloride; anionic surfactants such as sodium dodecyl sulfate; and nonionic surfactants such as polyoxyethylene alkyl ethers.
[0048] In the gelation step, the precursor sol prepared in the sol preparation step is poured into a gelation vessel and gelled at a temperature at which the sol-gel transition is likely to proceed, for example, at about 40° C. Here, since the precursor sol contains the above-mentioned coexisting substance that acts to induce the sol-gel transition and phase separation in parallel, spinodal decomposition is induced, and a porous structure of a silica hydrogel (wet gel) phase and a solvent phase is gradually formed.
[0049] In the gelation step, even after the silica hydrogel layer is formed, the polycondensation reaction of the wet gel proceeds slowly, causing the gel to shrink. Therefore, as a step following the gelation step (post-gelation step), the porous structure of the silica hydrogel phase and the solvent phase formed in the pores of the sol container in the gelation step is immersed in a basic aqueous solution such as ammonia water and heat-treated in a pressurized container. This allows the hydrolysis reaction, polycondensation reaction, and dissolution-reprecipitation reaction of the silica hydrogel phase to proceed further, making it possible to further strengthen the skeleton structure of the silica hydrogel phase. The "porous structure" referred to here means (1) a co-continuous structure of the silica hydrogel phase and the solvent phase (a mesh-like porous structure in which the skeleton forming the through holes has a three-dimensionally continuous space, also called a "three-dimensional continuous mesh structure"), or (2) a particle structure of the silica hydrogel phase. The post-gelation step may be performed as necessary. The heat treatment does not necessarily have to be performed in a pressurized container or a closed container. Since the heat treatment may generate or volatilize ammonia components, it is preferable to carry out the treatment in a closed container or a pressurized container having pressure resistance.
[0050] The pore size formed in the skeleton of the silica hydrogel phase is enlarged by the progress of the dissolution and reprecipitation reaction of the silica fine particles. Furthermore, the dissolution and reprecipitation reaction is repeated by hydrothermal treatment, so that the pore size can be further enlarged. The pore size can also be controlled by adding urea to the precursor sol in addition to the catalyst and coexisting substances. Urea is hydrolyzed at a temperature of 60° C. or higher to generate ammonia, and the pore size of the pores formed in the skeleton of the wet gel synthesized in the gelation process is enlarged by the ammonia, so that the pore size can be controlled by adding urea. On the other hand, the structure and pore size of the through holes can be controlled by adjusting the amount of water or silica precursor added to the precursor sol in the sol preparation process, or the composition and amount of the coexisting substance added.
[0051] Subsequently, in the removal step, the wet gel is washed and dried or dried only to remove the solvent phase containing additives, unreacted substances, etc. The space after the removal of the solvent phase becomes a through hole. By washing, the surface tension during drying caused by additives and unreacted substances remaining in the solvent phase is eliminated, and distortion and cracking of the gel during drying can be suppressed. The cleaning liquid is preferably a liquid such as an organic solvent or an aqueous solution. A liquid in which an organic compound or an inorganic compound is dissolved can also be used. Furthermore, even if a solution with a pH different from the isoelectric point of the gel, such as an acid or an alkali, is used as the cleaning liquid, the additives remaining in the gel can be easily removed. Specifically, acids such as hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid, acetic acid, formic acid, carbonic acid, citric acid, phosphoric acid, etc.; bases such as sodium hydroxide, potassium hydroxide, ammonia, water-soluble amine, sodium carbonate, and sodium bicarbonate can be used. The wet gel may be dried by natural drying, or, in order to eliminate distortion or cracks that may occur when drying the wet gel, it is preferable to dry the wet gel by replacing the solvent in the wet gel with a low surface tension solvent such as isopropanol, acetone, hexane, or hydrofluorocarbon, which has a lower surface tension than water, by drying using freeze sublimation, or by supercritical drying, which is performed in a surface tension-free state after replacing the solvent in the wet gel with carbon dioxide in a supercritical state.
[0052] Subsequently, the obtained dry gel can be sintered by firing to form silica glass. Note that if the firing temperature is lower than the glass transition temperature of silica (about 1000 °C), silica glass cannot be formed.
[0053] Through the above sol preparation process, gelation process, and removal process, a monolithic porous body made of silica gel or silica glass with a three-dimensional continuous network structure can be obtained.
[0054] The granulation process is a process of crushing and granulating the monolithic porous body obtained through the above sol preparation process, gelation process, and removal process. The pulverization treatment in the granulation process may be carried out manually, may use a mortar or the like, or may use a crushing device such as a ball mill. Also, in the case of sintering the dry gel obtained in the above removal process, the granulation process may be carried out either before or after the sintering.
[0055] The granulated monolithic porous body after the granulation process is sieved and classified with a sieve having an aperture of X μm and Y μm (where D0 ≦ X < Y ≦ 1000), and is recovered as porous particles having a particle diameter Dp within a desired particle diameter range (not less than D0 μm and not more than 4000 μm). However, the lower limit value D0 (μm) of the desired particle diameter range is the larger value of either 1 (μm) or 5 times the most frequent pore diameter (μm) of the pore size distribution of the through holes.
[0056] In the present invention, as described above, the pore diameter, through-hole diameter, and particle diameter can be independently controlled. The most frequent pore diameter (μm) of the pore size distribution of the through holes is defined as not less than 5 times the most frequent pore diameter (nm) of the pore size distribution of the pores, and the particle diameter (μm) is defined as not less than 5 times the most frequent pore diameter (μm) of the pore size distribution of the through holes. The reason is based on the empirically understood fact that in order for the skeleton body of each particle of the porous particles to maintain a skeleton structure having through holes even after granulation, a dimensional ratio of at least about 5 times is required between the pore diameter and the through-hole diameter, and between the through-hole diameter and the particle diameter, respectively.
[0057] The porous particles used in each of the examples are all porous particles of silica gel (also referred to as "porous silica particles") produced by the above-mentioned production method, i.e., through a synthesis step by a sol-gel method for a monolithic porous body and a granulation step.
[0058] More specifically, the silica monolith (manufactured by SNG Corporation, lot number: E087), which is a monolith-type porous body used in each example, was prepared as follows. 3 0.9 g of polyethylene glycol (molecular weight 100000) as a coexisting substance was dissolved in 0.1 M ammonia water, 7 mL of tetraethoxysilane (TEOS, silica precursor) was added, and the mixture was stirred to obtain a homogeneous solution, which was then gelled at 40°C. The gel was then immersed in 0.1 M ammonia water and heated at 100°C for 24 hours in a sealed container, and then sintered at 600°C for 5 hours. The obtained silica monolith was crushed in a mortar and classified using a JIS standard sieve to have a particle size within a predetermined range for each example, to obtain silica porous particles. In each example, the through-hole diameter was controlled by increasing or decreasing the amount of polyethylene glycol added, and the pore diameter was controlled by adjusting the temperature and time of heating with 0.1 M ammonia water.
[0059] In the present invention, the skeleton of the porous particle is preferably composed of an organic compound or an inorganic compound, and more preferably composed of an inorganic compound from the viewpoints of improving the strength, heat resistance, and chemical resistance of the porous particle.
[0060] When the skeleton of the porous particle is composed of an inorganic compound, examples of the inorganic compound include oxides and nitrides containing typical metal elements or transition metal elements such as silica (silica gel or silica glass), titania (TiO2), alumina (Al2O3), zirconia (ZrO2), hafnia (HfO2), germanium oxide (GeO2), silicon nitride (SiN), alumina nitride (AlN), and gallium nitride (GaN); oxides and nitrides containing alkali metal elements and alkaline earth metal elements such as lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), and barium (Ba); and complexes of these containing typical elements such as boron (B), carbon (C), phosphorus (P), and sulfur (P). In addition, examples of inorganic compounds other than these include (OSi(CH3)2). n It is preferable that the inorganic compound constituting the skeleton of the porous particle is not decomposed by the reaction.
[0061] Among the above inorganic compounds, silica, titania, alumina, zirconia and hafnia are preferred, and silica and titania are more preferred, from the viewpoints of chemical resistance, heat resistance, pressure resistance and the like.
[0062] In the present invention, the framework of the porous particles is more preferably silica and titania, and particularly preferably silica. That is, in the present invention, the porous particles are more preferably silica porous particles and titania porous particles, and particularly preferably silica porous particles.
[0063] When the skeleton of the porous particle is composed of an organic compound, examples of the organic compound include polystyrene, polyurethane, polyacrylic acid, polymethacrylic acid, polyacrylonitrile, polyacrylic, polystyrene-divinylbenzene copolymer, resorcinol-formaldehyde copolymer, graphite, and carbon materials made from carbon nanotubes.
[0064] Among the above organic compounds, polystyrene-divinylbenzene copolymer and polyacrylic are preferred from the viewpoints of improving the strength of the porous particles and surface processability.
[0065] In the present invention, the particle size of the porous particles is preferably from 20 μm to 720 μm, more preferably from 20 μm to 7500 μm, even more preferably from 20 μm to 300 μm, and particularly preferably from 20 μm to 100 μm, from the viewpoints of ease of packing into a powder-packed column, gas permeability, and the like.
[0066] The particle size of the porous particles can be measured using an optical microscope, a scanning electron microscope, a sieve with openings standardized by ISO3310 or JISZ8801-1, a particle size distribution meter, or the like.
[0067] The bulk density of the porous particles is appropriately determined depending on the material and porosity of the porous particles. From the viewpoint of ease of mixing with fine powders, the bulk density is preferably 0.05 to 7.5 (mg / mm 3 ), and 0.1 to 6 (mg / mm 3 ) is more preferable, and 0.15 to 5 (mg / mm 3 ), more preferably 0.2 to 3 (mg / mm 3 ) is particularly preferred.
[0068] When the skeleton of the porous particle is made of silica (SiO2), the bulk density of the porous particle is 0.05 to 1.65 (mg / mm 3 ), and 0.1 to 1.65 (mg / mm 3 ) is more preferable, and 0.15 to 1.65 (mg / mm 3 ) is more preferable. Here, 1.65 (mg / mm 3 ) is the true density of silica (SiO2) of 2.2 (mg / mm 3 ) and since the void fraction in close packing is 25%, it can be calculated uniquely as 2.2 × (1 – 0.25) = 1.65.
[0069] When the skeleton of the porous particles is made of titania (TiO2), the bulk density of the porous particles is 0.05 to 3.15 (mg / mm3 ), and 0.1 to 3.15 (mg / mm 3 ) is more preferable, and 0.15 to 3.15 (mg / mm 3 ) is more preferable. Here, 3.15 (mg / mm 3 ) is the true density of titania (TiO2) of 4.2 (mg / mm 3 Since the porosity of the closest packed structure is 25%, the value can be calculated uniquely as 4.2 × (1 − 0.25) = 3.15.
[0070] When the skeleton of the porous particles is made of hafnia (HfO2), the bulk density of the porous particles is 0.05 to 7.26 (mg / mm 3 ), and 0.1 to 7.26 (mg / mm 3 ) is more preferable, and 0.15 to 7.26 (mg / mm 3 ) is more preferable. Here, 7.26 (mg / mm 3 ) is the true density of hafnia (HfO2) of 9.68 (mg / mm 3 ) and since the void fraction in close packing is 25%, it can be calculated uniquely as 9.68 × (1 – 0.25) = 7.26.
[0071] (Method of tapping porous particles) The bulk density of porous particles means the hardened bulk density obtained after mechanically tapping a container (e.g., a quartz tube filled with quartz wool) containing the porous particles. The tapping method is performed in accordance with the method specified in the 16th Revised Japanese Pharmacopoeia, 3.01, Bulk Density and Tapped Density Measurement Method. The bulk density of porous particles is obtained by mechanically tapping a container containing the porous particles. Specifically, after measuring the initial mass of the porous particles placed in a container, the container is mechanically tapped and the mass is read until almost no mass change is observed. The value obtained by dividing the mass at this time by the volume of the container is the bulk density of the porous particles.
[0072] The average primary particle diameter (nm) of the fine powder is 1 nm or more, and is 80% or less of the most frequent pore diameter (μm) of the pore diameter distribution of the through holes. If the average primary particle diameter of the fine powder is less than 1 nm, it is difficult to produce the fine powder. When the average primary particle diameter of the fine powder exceeds 80% of the most frequent pore diameter in the pore diameter distribution of the through holes, the fine powder does not enter the through holes and the through holes are blocked, causing clogging of the fine powder in the through holes, preventing fluid from flowing in the through holes and making it impossible to reduce pressure loss. Also, when the primary particles of the fine powder aggregate to form secondary particles, aggregated particles, and agglomerated particles, there is no problem in using the above average primary particle diameter as the diameter of the secondary particles, aggregated particles, and agglomerated particles.
[0073] The average primary particle size of the fine powder is preferably 0.07% to 10% of the most frequent pore size in the pore size distribution of the through holes, and more preferably 0.1% to 1%.
[0074] The average primary particle size of the fine powder is preferably 3 nm or more and 75 nm or less, and more preferably 5 nm or more and 30 nm or less.
[0075] The average primary particle diameter of the fine powder is preferably 3 nm to 75 nm and 0.07% to 10% of the most frequent pore diameter in the pore diameter distribution of the through holes, more preferably 5 nm to 30 nm and 0.1% to 1% of the most frequent pore diameter in the pore diameter distribution of the through holes.
[0076] In the present invention, a commercially available fine powder is used, and the average primary particle diameter of the fine powder is the guaranteed value provided by the manufacturer. If the guaranteed value is not clear, a transmission electron microscope (TEM) is used to directly measure the distribution of the diameters of the primary particles of the fine powder. Specifically, an image is taken so that 20 or more particles of the fine powder are displayed in the image. From the transmission electron microscope photograph of the fine powder taken, the circle equivalent diameters of 20 primary particles are measured, and the arithmetic average is taken as the diameter. The calculation is performed assuming that the overall particle diameter is uniform throughout.
[0077] Examples of fine powders include powders of nanoparticle metal oxides, nanocarbons, nanoparticle catalysts, MOFs, metal complexes, low molecular weight organic compounds, enzymes, proteins, peptides, nucleic acids, and the like, or complexes thereof.
[0078] As the nanoparticle metal oxide, for example, titanium oxide, silicon oxide (silica), aluminum oxide (alumina), zinc oxide, strontium titanate, iron oxide, cerium oxide, zirconium oxide, etc. are preferably used.
[0079] As the nanocarbon, for example, graphene, graphene oxide, fullerene, carbon nanotube, etc. are preferably used.
[0080] As the nanoparticle catalyst, for example, a catalyst in which the above-mentioned nanoparticle oxide supports nanoparticles of a noble metal such as gold, platinum, or palladium is preferably used.
[0081] As the MOF powder, for example, MOF-5, MOF-177, HKUST-1, etc. are preferably used.
[0082] Suitable examples of metal complexes include scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, molybdenum, tungsten, ruthenium, osmium, rhodium, iridium, palladium, platinum, silver, gold, cadmium, mercury, and lanthanoids, and suitable ligands include ammine, carbonyl, phosphine, and thiol complexes.
[0083] As the low molecular weight organic compound, for example, proline and its derivatives, MacMillan catalyst, asymmetric phase transfer catalyst, thiourea, N-heterocyclic carbene, etc. are preferably used.
[0084] As the enzyme, for example, pepsin, trypsin, chymotrypsin, catalase, etc. are preferably used.
[0085] As the peptide, for example, D-proline-tyrosine-phenylalanine, proline-D-proline-2-aminoisobutyric acid-tryptophan-tryptophan-polyleucine acid, etc. are preferably used.
[0086] As the nucleic acid, for example, DNA, RNA, etc. are preferably used.
[0087] The bulk density of the fine powder is determined appropriately depending on the material and porosity of the fine powder, but is generally 0.02 to 7.5 (mg / mm 3 ), and 0.03 to 6 (mg / mm 3 ) is more preferable, and 0.04 to 4.5 (mg / mm 3 ), more preferably 0.05 to 3 (mg / mm 3 ) is particularly preferred.
[0088] When the fine powder is titanium oxide (TiO2), the bulk density of the fine powder is 0.02 to 3.15 (mg / mm 3 ), and 0.03 to 3.15 (mg / mm 3 ) is more preferable, and 0.04 to 3.15 (mg / mm 3 ), more preferably 0.05 to 3.15 (mg / mm 3 ) is particularly preferred. 3 ) is the true density of titanium dioxide (TiO2) of 4.2 (mg / mm 3 Since the porosity of the closest packed structure is 25%, the value can be calculated uniquely as 4.2 × (1 − 0.25) = 3.15.
[0089] When the fine powder is silica (SiO2), the bulk density of the fine powder is 0.02 to 1.65 (mg / mm 3 ), and 0.03 to 1.65 (mg / mm 3 ) is more preferable, and 0.04 to 1.65 (mg / mm 3 ), more preferably 0.05 to 1.65 (mg / mm 3 ) is particularly preferred. 3 ) is the true density of silica (SiO2) of 2.2 (mg / mm3 ) and since the void fraction in close packing is 25%, it can be calculated uniquely as 2.2 × (1 – 0.25) = 1.65.
[0090] When the fine powder is hafnia (HfO2), the bulk density of the fine powder is 0.02 to 7.26 (mg / mm 3 ), and 0.03 to 7.26 (mg / mm 3 ) is more preferable, and 0.04 to 7.26 (mg / mm 3 ), more preferably 0.05 to 7.26 (mg / mm 3 ) is particularly preferred. 3 ) is the true density of hafnia (HfO2) of 9.68 (mg / mm 3 ) and since the void fraction in close packing is 25%, it can be calculated uniquely as 9.68 × (1 – 0.25) = 7.26.
[0091] (Method of tapping fine powder) The bulk density of a fine powder means the hardened bulk density obtained after mechanically tapping a container (e.g., a quartz tube filled with quartz wool) containing the fine powder. The tapping method is performed in accordance with the method specified in the 16th Revised Japanese Pharmacopoeia, 3.01, Bulk Density and Tapped Density Measurement Method. The bulk density of a fine powder is obtained by mechanically tapping a container containing the fine powder. Specifically, after measuring the initial mass of the fine powder placed in a container, the container is mechanically tapped and the mass is read until almost no change in mass is observed. The value obtained by dividing the mass at this time by the volume of the container is the bulk density of the fine powder.
[0092] In the present invention, since the fine powder enters the through-holes of the porous particles or forms a catch on the surface of the through-holes, it is believed that the porous particles and the fine powder can be mixed uniformly without separation when mixed together. As a result, the filling of the fine powder near the porous particles is disturbed, and the through-holes are not clogged with the fine powder, allowing the fluid to flow effectively through the through-holes. It is believed that when gas or liquid is passed through a pipe having a packed layer formed of a mixture of the porous particles and the fine powder, the pressure loss can be significantly reduced.
[0093] The packed bed of the present invention is formed from a mixture of porous particles and fine powder. As a method for preparing a mixture by mixing the porous particles and fine powder, a known method such as a dry mixing method or a wet mixing method can be adopted.
[0094] In the case of dry mixing, any method, whether manual or mechanical, based on the principle of shaking, shaking, rotating, stirring, etc., can be used as long as the porous structure of the porous particles is not destroyed.
[0095] In the case of wet mixing, various similar mixing methods can be employed after adding a solvent.
[0096] From the viewpoint of uniformly mixing the porous particles and the fine powder, the mixing ratio of the porous particles to the fine powder in the packed bed of the present invention is preferably a porous particles / fine powder weight ratio of 20 / 80 to 80 / 20, more preferably a 25 / 75 to 75 / 25 weight ratio, even more preferably a 30 / 70 to 70 / 30 weight ratio, and particularly preferably a 35 / 65 to 65 / 35 weight ratio.
[0097] The bulk density of the packed bed of the present invention is primarily determined depending on the mixed state of the porous particles and the fine powder. From the viewpoint of ensuring good contact of the fluid with the fine powder, the bulk density is preferably in the same range as that of the porous particles and the fine powder, that is, 0.05 to 7.5 (mg / mm 3 ), and 0.1 to 6 (mg / mm 3 ) is more preferable, and 0.15 to 3 (mg / mm 3), more preferably 0.2 to 2 (mg / mm 3 ) is particularly preferred.
[0098] (Method of tapping a mixture of porous particles and fine powder) The bulk density of the packed bed means the hardened bulk density obtained after mechanically tapping a container (e.g., a quartz tube filled with quartz wool) containing a mixture of porous particles and fine powder. The tapping method is performed in accordance with the method specified in the 16th Revised Japanese Pharmacopoeia, 3.01, Bulk Density and Tapped Density Measurement Method. The bulk density of the packed bed is obtained by mechanically tapping a container containing a mixture of porous particles and fine powder. Specifically, after measuring the initial mass of the mixture of porous particles and fine powder placed in the container, the container is mechanically tapped and the mass is read until almost no mass change is observed. The value obtained by dividing the mass at this time by the volume of the container is the bulk density of the packed bed.
[0099] The packed bed of the present invention is preferably used as a packing filled in a tube.
[0100] The tube may be, for example, a quartz tube, a glass tube, a resin tube, a metal tube, or the like.
[0101] The packed bed of the present invention can be used, for example, as a catalytic reactor, a photocatalytic reactor, an adsorption column, a chromatography column, etc. by being packed into a column.
[0102] The packed bed of the present invention is also widely used as a filter (for example, an exhaust gas purification filter, an air purification filter, a water purification filter, etc.).
[0103] The packed bed of the present invention can be used for gas-phase catalytic reactions, liquid-phase catalytic reactions, gas-phase photocatalytic reactions, liquid-phase photocatalytic reactions, adsorption separation, adsorption removal, and the like.
[0104] In the present invention, the mixture in the packed bed preferably further contains enzyme particles. That is, the packed bed of the present invention is preferably formed from a mixture of porous particles, fine powder, and enzyme particles. By being provided with such a configuration, the present invention (1) maintains catalytic activity, and (2) enables dynamic optical resolution with high efficiency, high yield, and high optical purity.
[0105] In the present invention, it is preferable that the mixture ratio of the porous particles and the fine powder in the packed bed formed from a mixture of the porous particles and the fine powder changes stepwise.
[0106] In the present invention, it is preferable that the mixture ratio of the fine powder and the enzyme particles in the packed bed formed from a mixture of the porous particles, the fine powder and the enzyme particles changes stepwise.
[0107] In the present invention, a packed bed formed of a mixture of porous particles and fine powder is divided into a first region, a second region, and a third region in this order from the upstream side to the downstream side in the flow direction of the liquid, (1) the first region is filled with fine powder and porous particles such that a mixing ratio of the fine powder to the porous particles is [fine powder] / [porous particles]=1 / 1 to 1 / 17 (weight ratio); (2) the second region is filled with fine powder and porous particles such that the mixing ratio of the fine powder to the porous particles is [fine powder] / [porous particles]=1 / 0.5 to 1 / 10 (weight ratio); (3) It is preferable that the third region is filled with fine powder and porous particles such that the mixing ratio of the fine powder to the porous particles is [fine powder] / [porous particles] = 1 / 0.25 to 1 / 10 (weight ratio).
[0108] In the present invention, a packed bed formed of a mixture of porous particles, fine powder, and enzyme particles is divided into a first region, a second region, and a third region from the upstream side to the downstream side in the flow direction of the liquid, (1) The first region is filled with fine powder and enzyme particles such that the mixing ratio of the fine powder to the enzyme particles is [fine powder] / [enzyme particles]=1 / 3 to 1 / 34 (weight ratio); (2) the second region is filled with fine powder and enzyme particles such that the mixing ratio of the fine powder to the enzyme particles is [fine powder] / [enzyme particles]=1 / 2 to 1 / 20 (weight ratio); (3) It is preferable that the third region is filled with fine powder and enzyme particles so that the mixing ratio of the fine powder to the enzyme particles is [fine powder] / [enzyme particles] = 1 / 1.4 to 1 / 20 (weight ratio).
[0109] In the present invention, for example, the enzyme particles are preferably lipase.
[0110] The present invention relates to a packed bed formed of a mixture of porous particles, fine powder and lipase, (1) The porous particle has a skeleton, through holes formed in gaps in the skeleton, and a plurality of pores extending from the surface of the skeleton toward the inside, the most frequent pore size in the pore size distribution of the through holes is 0.1 μm or more and 100 μm or less, and the particle size of the porous particles is 20 μm or more and 3000 μm or less, the most frequent pore size in the pore size distribution of the pores is 1 nm or more and 200 nm or less, and is 20% or less of the most frequent pore size in the pore size distribution of the through holes; (2) It is preferable that the average primary particle diameter of the fine powder is 1 nm or more and is 80% or less of the most frequent pore diameter in the pore diameter distribution of the through holes of the porous particles.
[0111] 2. Distribution method The present invention is a method for passing a gas or liquid through a pipe provided with the above-mentioned packed bed.
[0112] Examples of gases include nitrogen, oxygen, helium, argon, hydrogen, carbon monoxide, carbon dioxide, air, gaseous compounds, and mixtures of these.
[0113] Examples of the liquid include water, organic solvents, ionic liquids, and mixtures of the two.
[0114] Examples of water that can be used include natural water, purified water, distilled water, ion-exchanged water, pure water, tap water, river water, pond water, sewage water, seawater, etc. Among these waters, distilled water and ion-exchanged water are preferred.
[0115] As the organic solvent, a conventionally known organic solvent can be used. Examples of such organic solvents include alcohols, ketones, esters, hydrocarbons, and ethers. Examples of alcohols include methanol, ethanol, and isopropyl alcohol. Examples of ketones include acetone and methyl ethyl ketone. Examples of esters include ethyl acetate and isopropyl acetate. Examples of hydrocarbons include cyclohexane, n-hexane, and n-octane. Examples of ethers include diethyl ether and dimethyl ether. The organic solvent is not limited to these organic solvents. In addition, it may be used as a mixed solvent with a polar organic solvent that has affinity with water, and as a mixed solvent of water and an organic solvent, for example, an organic substance with high viscosity may be used as an aqueous solution, and examples of such a mixed solvent include an aqueous glycerin solution and a 70% aqueous ethanol solution.
[0116] The amount of gas supplied when passing the gas through a tube equipped with a packed bed is defined as the space velocity (SV), and is preferably 100 to 100,000 / hr. The SV can be calculated by dividing the amount of gas supplied per hour by the void volume in the column.
[0117] The amount of liquid supplied when the liquid is passed through a tube equipped with a packed bed is defined as contact time (CT), and is preferably 0.1 to 3600 seconds. The CT here can be calculated by (void volume in the column)÷(amount of liquid supplied per second), or (column length)÷(linear velocity of the liquid per second).
[0118] The packed bed of the present invention can be used in a catalyst column.
[0119] The catalytic column is preferably a catalytic column for optical resolution. EXAMPLES
[0120] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the examples.
[0121] Comparative Example 1 A quartz tube (having claws for holding the quartz wool) with an outer diameter of 8 mm, an inner diameter of 6 mm, and a length of 340 mm was filled with 20 mg of quartz wool (fiber thickness 2 to 6 μm, manufactured by Tosoh Corporation) as a support. 50 mg of fine powder of titanium oxide (manufactured by Nippon Aerosil Co., Ltd., product name: AEROXIDE (registered trademark) TiO2P25, average primary particle diameter by transmission electron microscope observation: 21 nm) was filled on the quartz wool as particles 1. Then, tapping was performed according to the above-mentioned fine powder tapping method. Tapping was performed by dropping the quartz tube filled with particles 1 from a height of 10 mm at 60 times / min 200 times, until the length of the packed bed did not change after each 200 times. As a result, a packed bed of particles 1 with a length of 15 mm was obtained by tapping.
[0122] The quartz tube with the packed bed was attached to a gas flow device (product name: TP-5000, manufactured by Henmi Slide Rule Co., Ltd. (formerly Okura Riken Co., Ltd.)) and He gas was passed through the mass flow controller at a flow rate of 0 to 100 mL / min in increments of 10 mL / min, while the gas pressure upstream of the packed bed was measured with a pressure gauge (electronic pressure transmitter PT3000, manufactured by Okura Electric Co., Ltd.). The measurement range of the pressure gauge was 0 to 980 kPa (gauge pressure, display resolution 1 V, accuracy ±0.25% FS). The outlet of the quartz tube was open to the atmosphere, so the indicated value (kPa) on the pressure gauge was defined as the pressure loss (kPa) across the packed bed. The pressure loss due to the quartz wool alone was ignored because the indicated value (kPa) on the pressure gauge remained 0 kPa even when 100 mL / min of He gas was passed through. When the He gas flow rate was increased from 0 mL / min to 100 mL / min in increments of 10 mL / min, the pressure drop increased to 18 kPa. Next, the He gas flow rate was decreased to 0 mL / min in increments of 10 mL / min, and the cycle of increasing and decreasing the He gas flow rate was repeated three times in total. The changes in pressure drop in the second and third cycles were consistent.
[0123] Figure 4 shows the change in pressure drop versus He gas flow rate. As shown in Figure 4, hysteresis was observed, where the pressure was higher when the He gas flow rate was decreased (dotted line) than when the He gas flow rate was increased (solid line). After the third cycle was completed, the length of the packed bed of particle 1 was measured and found to be 13 mm. This length of the packed bed was designated L1. Furthermore, the bulk density of particle 1 was calculated to be 0.14 (mg / mm 3 ) was calculated. Bulk density of particle 1 (mg / mm 3 ) = Weight of particle 1 (mg) / [Length of packed bed L1 (mm) × Cross-sectional area of quartz tube (mm 2 )]
[0124] In the following Examples 1 and 2 and Comparative Examples 2 and 3, the weight of the titanium oxide fine powder (particle 1) was 50 mg and the bulk density was 0.14 (mg / mm 3 ) and the length (L1) of the packed bed of particles 1 was adjusted to 13 mm in all cases.
[0125] Example 1 As in Comparative Example 1, 20 mg of quartz wool (fiber thickness 2 to 6 μm, manufactured by Tosoh Corporation) was packed as a support in a quartz tube (outer diameter 8 mm, inner diameter 6 mm, length 340 mm). Next, silica monolith (manufactured by SNG Corporation, lot number: E087) was pulverized using a mortar to obtain silica porous particles as particles 2. Thereafter, the particle size of particles 2 was uniformed in the range of 500 to 710 μm by sieving using a stainless steel sieve of JIS Z8801-1 (two types of mesh size: 510 μm and 710 μm). The surface of particles 2 with uniform particle size was photographed with a scanning electron microscope (manufactured by JEOL, product name: JSM-6510). From the SEM photograph of the photographed particle 2 (FIG. 1(a)), the pore size distribution of the through holes of particle 2 was created according to the above-mentioned "method of creating a pore size distribution of through holes in porous particles" (FIG. 1(b)). As shown in Figure 1(b), the most frequent pore size in the pore size distribution of the through-holes of Particle 2 was 10 μm. For Particle 2 with a uniform particle size, a nitrogen adsorption / desorption device (manufactured by Japan Microtrack-Bell, product name: BELSORP-mini II) was used to create a pore size distribution of the pores derived by the BJH method through nitrogen adsorption measurement (Figure 2). As shown in Figure 2, the most frequent pore size in the pore size distribution of Particle 2 was 6 nm.
[0126] Next, as a preliminary step, the amount of particles 2 with a uniform particle size in the range of 500 to 710 μm was determined as follows. First, 200 mg of quartz wool was packed as a support in a quartz tube, as in Comparative Example 1. Then, particles 2 with a uniform particle size were packed on the quartz wool, and tapping was performed while adjusting the amount of particles 2 packed according to the above-mentioned tapping method for porous particles. The tapping was performed by dropping the quartz tube filled with particles 2 from a height of 10 mm at 60 times / min 200 times, and was performed until the length of the packed bed did not change after each 200 times. As a result, a packed bed of particles 2 with a length of 13 mm was obtained by tapping. The length of this packed bed was designated as L2. Since the weight of particles 2 at this time was 72 mg, the amount of particles 2 used was determined to be 72 mg. Furthermore, the bulk density of particles 2 was calculated to be 0.20 (mg / mm 3 ) was calculated. Bulk density of particle 2 (mg / mm 3) = Weight of particle 2 (mg) / [Length of packed bed L2 (mm) × Cross-sectional area of quartz tube (mm 2 )]
[0127] 50 mg of titanium oxide fine powder (manufactured by Nippon Aerosil Co., Ltd., trade name: AEROXIDE (registered trademark) TiO2P25, average primary particle diameter: 21 nm) as particle 1 and 72 mg of silica porous particles (most frequent pore size distribution of through holes: 10 μm, most frequent pore size distribution of fine pores: 6 nm, particle size: 500 to 710 μm) as particle 2 were placed in a 6 mL screw tube bottle (manufactured by AS ONE Corporation, No. 2) and the bottle was lidded and mixed by shaking well by hand to obtain a mixture of particles 1 and 2. Next, 20 mg of quartz wool was packed into a quartz tube, and the mixture of particles 1 and 2 was filled on the quartz wool, and tapping was performed according to the tapping method for the mixture of porous particles and fine powder described above. Tapping was performed by dropping a quartz tube filled with a mixture of particles 1 and 2 from a height of 10 mm at 60 times / min 200 times, until the length of the packed bed did not change after each 200 times. As a result, a packed bed of 22 mm in length consisting of a mixture of particles 1 and 2 was obtained by tapping. The length of this packed bed was designated as L. The quartz tube with the packed bed was then attached to a gas flow device (manufactured by Henmi Slide Rule Co., Ltd., product name: TP-5000), and He gas was passed through it under the same conditions as in Comparative Example 1.
[0128] As shown in FIG. 4, even with a He gas flow rate of 100 mL / min, the pressure loss was 6 kPa. Although the length of the packed bed was about twice as long as that of Comparative Example 1, the pressure loss was significantly reduced. Furthermore, there was no difference in pressure change between the first and second cycles of increasing and decreasing the He gas flow rate, and no hysteresis was observed between when the He gas flow rate was increased (solid line) and when the He gas flow rate was decreased (dotted line). After the second cycle was completed, the length of the packed bed was measured to be 22 mm, which was the same as the length of the packed bed before the He gas flow (L: 22 mm). Furthermore, the bulk density of the packed bed was calculated to be 0.20 (mg / mm 3 ) was calculated. Bulk density of packed bed (mg / mm 3) = [Weight of particle 1 (mg) + Weight of particle 2 (mg)] / [Length of packed bed L (mm) × Cross-sectional area of quartz tube (mm 2 )]
[0129] Example 2 Except for adjusting the particle size of the silica porous particles to 212 to 500 μm, 50 mg of titanium oxide fine powder (manufactured by Nippon Aerosil Co., Ltd., product name: AEROXIDE (registered trademark) TiO2P25, average primary particle size: 21 nm) was prepared as particle 1 in the same manner as in Example 1, and 50 mg of silica porous particles (mode diameter of through hole diameter distribution: 10 μm, mode diameter of fine pore diameter distribution: 6 nm, particle size: 212 to 500 μm, bulk density: 0.20 mg / mm) was prepared as particle 2. 3 ) was mixed with 73 mg of the above to obtain a mixture of particles 1 and particles 2.
[0130] A quartz tube (outer diameter 8 mm, inner diameter 6 mm, length 340 mm) was packed with 20 mg of quartz wool (fiber thickness 2 to 6 μm, manufactured by Tosoh Corporation), and a mixture of particles 1 and particles 2 was packed on the quartz wool. A packed bed was obtained by tapping in the same manner as in Example 1 according to the tapping method for the mixture of porous particles and fine powder described above. The length (L) of the packed bed was measured to be 22 mm. The quartz tube with the packed bed was attached to a gas distribution device (manufactured by Henmi Slide Rule Co., Ltd., product name: TP-5000), and He gas was passed through the device under the same conditions as in Comparative Example 1.
[0131] As shown in FIG. 4, the pressure loss was 3 kPa when the He gas flow rate was 100 mL / min, and it was confirmed that the pressure loss was lower than that of Example 1. The length of the packed bed after the pressure loss measurement was 22 mm, which was the same as the length of the packed bed before the He gas flow (L = 22 mm). Furthermore, from the same calculation formula as in Example 1, the bulk density of the packed bed was calculated to be 0.20 (mg / mm 3 ) was calculated.
[0132] Comparative Example 2 Quartz sand without through holes or pores (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., product number: 172-00015, product particle size: 600 to 850 μm at least 50%) was crushed using a mortar to obtain quartz sand as particles 2. Thereafter, the particle size of particles 2 was uniformed to the range of 500 to 710 μm by sieving using a JIS Z8801-1 stainless steel sieve (two types of mesh size: 510 μm and 710 μm).
[0133] Next, as a preliminary step, a quartz tube (outer diameter 8 mm, inner diameter 6 mm, length 340 mm) packed with 200 mg of quartz wool (fiber thickness 2 to 6 μm, manufactured by Tosoh Corporation) was used, and tapping was performed in the same manner as in Example 1 so that the length (L2) of the packed bed was 13 mm, and the amount of particles 2 with a uniform particle size was determined to be 508 mg. Furthermore, the bulk density of particles 2 was determined to be 1.38 (mg / mm 3 ) was calculated.
[0134] 50 mg of fine powder of titanium oxide (manufactured by Nippon Aerosil Co., Ltd., trade name: AEROXIDE (registered trademark) TiO2P25, average primary particle diameter: 21 nm) as particle 1 and 508 mg of particle 2 with a uniform particle size in the range of 500 to 710 μm were mixed in the same manner as in Example 1 to obtain a mixture of particle 1 and particle 2. Next, 20 mg of quartz wool was packed into a quartz tube, and the mixture of particle 1 and particle 2 was packed on the quartz wool, and a packed layer was obtained by tapping in the same manner as in Example 1. The length (L) of the packed layer was measured to be 23 mm. Then, the quartz tube with the packed layer was attached to a gas distribution device (manufactured by Henmi Slide Rule Co., Ltd., trade name: TP-5000), and He gas was distributed under the same conditions as in Comparative Example 1.
[0135] As shown in FIG. 4, the pressure loss was 13 kPa when the He gas flow rate was 100 mL / min. From this, it was confirmed that the pressure loss in Comparative Example 2 was lower than that in Comparative Example 1, and did not decrease to less than half of the pressure loss in Comparative Example 1. The length of the packed bed after the pressure loss measurement was 23 mm, which was the same as the length of the packed bed before the He gas flow (L = 23 mm). Furthermore, from the same calculation formula as in Example 1, the bulk density of the packed bed was calculated to be 0.86 (mg / mm 3) was calculated.
[0136] Comparative Example 3 Silica gel having no through holes but fine pores (manufactured by Fuji Silysia Chemical Ltd., product name: CALiACT (registered trademark) Q-15, particle size: 500 to 710 μm) was pulverized using a mortar to obtain silica gel as particles 2. Thereafter, the particle size of particles 2 was adjusted to a range of 500 to 710 μm by sieving using a JIS Z8801-1 stainless steel sieve (two types of mesh openings: 510 μm and 710 μm).
[0137] Next, as a preliminary step, a quartz tube (outer diameter 8 mm, inner diameter 6 mm, length 340 mm) packed with 200 mg of quartz wool (fiber thickness 2 to 6 μm, manufactured by Tosoh Corporation) was used, and tapping was performed in the same manner as in Example 1 so that the length (L2) of the packed bed was 13 mm, and the amount of particles 2 with a uniform particle size was determined to be 133 mg. Furthermore, the bulk density of particles 2 was determined to be 0.36 (mg / mm 3 ) was calculated.
[0138] 50 mg of titanium oxide fine powder (manufactured by Nippon Aerosil Co., Ltd., product name: aeroxide P25, average primary particle diameter: 20 nm) as particle 1 and 508 mg of particle 2 with a uniform particle size in the range of 500 to 710 μm were mixed in the same manner as in Example 1 to obtain a mixture of particle 1 and particle 2. Next, 20 mg of quartz wool was packed into a quartz tube, and the mixture of particle 1 and particle 2 was packed on the quartz wool, and tapping was performed in the same manner as in Example 1 to obtain a packed layer. The length (L) of the packed layer was measured to be 23 mm. Then, the quartz tube with the packed layer was attached to a gas distribution device (manufactured by Henmi Slide Rule Co., Ltd., product name: TP-5000), and He gas was distributed under the same conditions as in Comparative Example 1.
[0139] As shown in FIG. 4, the pressure loss was 11 kPa when the He gas flow rate was 100 mL / min. From this, it was confirmed that the pressure loss in Comparative Example 3 and that in Comparative Example 2 were comparable in value. It was also confirmed that the pressure loss in Comparative Example 3 did not decrease to less than half of the pressure loss in Comparative Example 1, in which only titanium oxide fine powder was used. The length of the packed bed after the pressure loss measurement was 23 mm, which was the same as the length of the packed bed before the He gas flow (L = 23 mm). Furthermore, from the same calculation formula as in Example 1, the bulk density of the packed bed was calculated to be 0.28 (mg / mm 3 ) was calculated.
[0140] The relationships between particles 1, particles 2, and the packed layer in Examples 1 and 2 and Comparative Examples 1 to 3 are shown in Table 1 below.
[0141] [Table 1]
[0142] 4, it is considered that in the porous silica particles of Examples 1 and 2, the porous silica particles having through holes are mixed into the packed layer of the titanium oxide fine powder, which causes a geometric effect that disturbs the packed state of the titanium oxide fine powder, resulting in the formation of large gaps in the interparticle voids of the particles 2. More specifically, it is considered that the presence of through holes in the porous silica particles causes the titanium oxide fine powder to disperse in the through holes of the porous silica particles, and the particles 1 that were present in the gaps between the particles 2 move into the gaps between the particles 2, thereby enlarging the gaps between the particles 2. It is presumed that for these reasons, a large pressure loss reduction effect was observed in Examples 1 and 2 compared to Comparative Examples 1 to 3.
[0143] Comparative Example 4 A quartz tube (outer diameter 8 mm, inner diameter 6 mm, length 340 mm) was filled with 20 mg of quartz wool (fiber thickness 2 to 6 μm, manufactured by Tosoh Corporation) as a support. 50 mg of silica fine powder (manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) 200, average primary particle diameter observed by transmission electron microscope: 12 nm) was filled on the quartz wool as particles 1. Thereafter, tapping was performed in the same manner as in Comparative Example 1 to obtain a packed bed with a length of 32 mm.
[0144] The quartz tube with the packed bed was attached to a gas flow device (manufactured by Henmi Slide Rule Co., Ltd., product name: TP-5000), and He gas was passed through it under the same conditions as in Comparative Example 1 to measure the pressure loss. A cycle of increasing the He gas flow rate and decreasing the He gas flow rate was repeated a total of three times, and the changes in pressure loss between the second and third cycles were consistent. The changes in pressure loss versus He gas flow rate at this time are shown in Figure 5.
[0145] As shown in Fig. 5, the pressure loss was 52 kPa when the He gas flow rate was 100 mL / min. As shown in Fig. 5, hysteresis was observed in which the pressure was higher when the He gas flow rate was decreased (dotted line) than when the He gas flow rate was increased (solid line). After the third cycle was completed, the length of the packed bed of the silica fine powder was measured and found to be 24 mm. This packed bed length was designated as L1. Furthermore, the bulk density of Particle 1 was calculated to be 0.07 (mg / mm 3 ) was calculated.
[0146] In the following Example 3, the weight of the silica fine powder (particle 1) was 50 mg and the bulk density was 0.07 (mg / mm 3 ) and the length (L1) of the packed bed of particles 1 was adjusted to 24 mm.
[0147] Example 3 As in Comparative Example 4, 20 mg of quartz wool (fiber thickness 2 to 6 μm, manufactured by Tosoh Corporation) was packed as a support in a quartz tube (outer diameter 8 mm, inner diameter 6 mm, length 340 mm). Next, titania monolith (manufactured by SNG Corporation, lot number: T5071) was pulverized using a mortar to obtain titania porous particles as particles 2. Thereafter, the particle size of particles 2 was uniformed in the range of 125 to 300 μm by sieving using a stainless steel sieve (with two types of mesh openings, 125 μm and 300 μm) conforming to JIS Z8801-1. The surface of particles 2 with uniform particle size was imaged using a scanning electron microscope (manufactured by JEOL, product name: JSM-6510). From the captured SEM photograph of particle 2 (Fig. 3(a)), the pore size distribution of the through holes of particle 2 was created (Fig. 3(b)) according to the above-mentioned "Method for creating the pore size distribution of through holes in porous particles". As shown in Fig. 3(b), the most frequent pore size in the pore size distribution of the through holes of particle 2 was 5 μm. For particles 2 with a uniform particle size, the most frequent pore size in the pore size distribution of the fine pores was 6 nm.
[0148] Next, as a preliminary step, the amount of particles 2 with a uniform particle size in the range of 125 to 300 μm to be used was determined as follows. First, 200 mg of quartz wool was packed as a support in a quartz tube in the same manner as in Example 1. Then, particles 2 with a uniform particle size were packed on the quartz wool, and tapping was performed until the length of the packed bed did not change in the same manner as in Example 1. Tapping was repeated while adjusting the amount of particles 2 packed so that the length (L2) of the packed bed became 24 mm. Since the weight at this time was 430 mg, the amount of particles 2 to be used was determined to be 430 mg. Furthermore, the bulk density of particles 2 was calculated to be 0.63 (mg / mm) from the following calculation formula. 3 ) was calculated. Bulk density of particle 2 (mg / mm 3 ) = Weight of particle 2 (mg) / [Length of packed bed L2 (mm) × Cross-sectional area of quartz tube (mm 2 )]
[0149] 50 mg of silica fine powder (manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) 200, average primary particle diameter by transmission electron microscope observation: 12 nm) as particle 1 and 430 mg of titania porous particles (most frequent pore diameter in through-hole pore diameter distribution: 5 μm, most frequent pore diameter in fine pore pore diameter distribution: 6 nm, particle size: 125 to 300 μm) as particle 2 were placed in a 6 mL screw tube bottle (manufactured by AS ONE Corporation, No. 2) and the bottle was lidded and mixed by shaking well by hand to obtain a mixture of particle 1 and particle 2. Next, 20 mg of quartz wool was packed into a quartz tube, and the mixture of particle 1 and particle 2 was filled on the quartz wool, and tapping was performed in the same manner as in Comparative Example 1 to obtain a packed bed. The length (L) of the packed bed was measured to be 46 mm. Thereafter, the quartz tube provided with the packed layer was attached to a gas flow device (manufactured by Henmi Slide Rule Co., Ltd., product name: TP-5000), and He gas was passed through the device under the same conditions as in Comparative Example 1.
[0150] As shown in FIG. 5, even at a flow rate of 100 mL / min, the pressure loss was 8 kPa. Although the length of the packed bed was about twice as long as that of Comparative Example 4, the pressure loss was significantly reduced. Furthermore, there was no difference in pressure change between the first and second cycles of increasing and decreasing the He gas flow rate, and no hysteresis was observed between when the He gas flow rate was increased (solid line) and when the He gas flow rate was decreased (dotted line). Furthermore, when the length of the packed bed was measured after the second cycle was completed, it was 46 mm, which was the same as the length of the packed bed before the He gas flow (L: 46 mm). Furthermore, from the following calculation formula, the bulk density of the packed bed was calculated to be 0.37 (mg / mm 3 ) was calculated. Bulk density of packed bed (mg / mm 3 ) = [Weight of particle 1 (mg) + Weight of particle 2 (mg)] / [Length of packed bed L (mm) × Cross-sectional area of quartz tube (mm 2 )]
[0151] The relationships between particles 1, particles 2, and the packed layer in Example 3 and Comparative Example 4 are shown in Table 2 below.
[0152] [Table 2]
[0153] Comparative Example 5 A quartz tube (outer diameter 8 mm, inner diameter 6 mm, length 340 mm) was packed with 20 mg of quartz wool (fiber thickness 2 to 6 μm, manufactured by Tosoh Corporation) as a support. 332 mg of titanium oxide fine powder (manufactured by Sigma-Aldrich, product name: P25, average primary particle diameter: 25 nm) was packed on the quartz wool as particles 1. Then, tapping was performed in the same manner as in Comparative Example 1 to obtain a packed layer with a length of 13 mm.
[0154] Example 4 332 mg of titanium oxide fine powder (Sigma-Aldrich, product name: P25, average primary particle diameter: 25 nm) as particle 1 and 60 mg of silica porous particles (the most frequent pore size distribution of through holes: 10 μm, the most frequent pore size distribution of fine pores: 6 nm, particle size: 1000 to 3000 μm, SNG Corporation, lot number: E093) as particle 2 were placed in a 6 mL screw tube bottle (As One Corporation, No. 2) and the bottle was closed and mixed by shaking well by hand to obtain a mixture of particles 1 and 2. Next, 20 mg of quartz wool was packed into a quartz tube, and the mixture of particles 1 and 2 was filled on the quartz wool, and tapping was performed according to the tapping method for the mixture of porous particles and fine powder described above. Tapping was performed by dropping a quartz tube filled with a mixture of particles 1 and 2 from a height of 10 mm at 60 times per minute 200 times, until the length of the packed bed did not change after each 200 times. As a result, a packed bed consisting of a mixture of particles 1 and 2 with a length of 20 mm was obtained by tapping.
[0155] Example 5 A packed bed was prepared in the same manner as in Example 4, except that the particle size of the porous silica particles as particles 2 was changed to 710 to 1000 μm. As a result, a packed bed consisting of a mixture of particles 1 and particles 2 and having a length of 21 mm was obtained by tapping.
[0156] Example 6 A packed bed was prepared in the same manner as in Example 4, except that the particle size of the porous silica particles as particles 2 was set to 212 to 710 μm. As a result, a packed bed consisting of a mixture of particles 1 and particles 2 and having a length of 20 mm was obtained by tapping.
[0157] Example 7 A packed bed was prepared in the same manner as in Example 4, except that the particle size of the porous silica particles as particles 2 was 20 to 212 μm. As a result, a packed bed consisting of a mixture of particles 1 and particles 2 and having a length of 19 mm was obtained by tapping.
[0158] For the quartz tubes with the packed beds obtained in Comparative Example 5 and Examples 4 to 7, a gas flow test was carried out in the same manner as in Comparative Example 1. However, argon gas was used instead of helium gas, and the pressure was measured when the argon gas flow rate was 100 mL / min. The measurement was repeated until no change in pressure loss was observed. The length of the packed beds obtained in Comparative Example 5 and Examples 4 to 7 before and after the argon gas flow was unchanged.
[0159] The relationships between particle 1, particle 2, and the packed layer in Examples 4 to 7 and Comparative Example 5 are shown in Table 1 below. In addition, for Examples 4 to 7 and Comparative Example 5, the bulk density of particle 1, the bulk density of particle 2, and the bulk density of the packed layer were calculated from the above-mentioned formulas, and the results are shown in Table 3.
[0160] [Table 3]
[0161] The length of the packed bed in Comparative Example 5 is different from that in Examples 4 to 7, and the pressure loss is linearly proportional to the length of the packed bed. Therefore, the pressure loss normalized to a packed bed length of 10 mm was used to compare the pressure loss between Comparative Example 5 and Examples 4 to 7. As shown in Table 3, the pressure loss normalized to a packed bed length of 10 mm was 83 kPa in Comparative Example 5, 33 kPa in Example 4, 15 kPa in Example 5, 26 kPa in Example 6, and 64 kPa in Example 7. From this, it was confirmed that the pressure loss can be reduced more than that of Comparative Example 5 by mixing particles 1 and particles 2 in Examples 4 to 7, even though the length of the packed bed in Examples 4 to 7 is about 1.5 times that of the packed bed in Comparative Example 5.
[0162] As shown in Table 3, the pressure loss was most reduced for the particle size of 710 to 1000 μm in Example 5, followed in order by the particle sizes of 212 to 710 μm in Example 6, the particle sizes of 1000 to 3000 μm in Example 4, and the particle sizes of 20 to 212 μm in Example 7. As a result, when the particle size range of the porous particles (particles 2) was 20 to 3000 μm, the pressure loss was reduced more than in Comparative Example 5.
[0163] Example 8 A packed bed was prepared in the same manner as in Example 4, except that 330 mg of brilliant blue-colored titanium oxide fine powder (manufactured by Sigma-Aldrich Corporation, product name: P25, average primary particle size: 25 nm) was used as particle 1, and 80 mg of silica porous particles (mode diameter of through-hole size distribution: 0.1 μm, mode diameter of fine pore size distribution: 6 nm, particle size: 200 to 700 μm, manufactured by SNG Corporation, lot number: PM105) was used as particle 2.
[0164] Example 9 A packed bed was prepared in the same manner as in Example 4, except that 330 mg of brilliant blue-colored titanium oxide fine powder (manufactured by Sigma-Aldrich Corporation, product name: P25, average primary particle size: 25 nm) was used as particle 1, and 80 mg of silica porous particles (mode diameter of through-hole size distribution: 1 μm, mode diameter of fine pore size distribution: 6 nm, particle size: 200 to 700 μm, manufactured by SNG Corporation, lot number: PM123) was used as particle 2.
[0165] Example 10 A packed bed was prepared in the same manner as in Example 4, except that 330 mg of brilliant blue-colored titanium oxide fine powder (manufactured by Sigma-Aldrich Corporation, product name: P25, average primary particle size: 25 nm) was used as particle 1, and 80 mg of silica porous particles (mode diameter of through-hole size distribution: 20 μm, mode diameter of fine pore size distribution: 6 nm, particle size: 200 to 700 μm, manufactured by SNG Corporation, lot number: E040) was used as particle 2.
[0166] Comparative Example 6 A packed bed was prepared in the same manner as in Example 4, except that 330 mg of fine powder of titanium oxide colored with brilliant blue (manufactured by Sigma-Aldrich Corporation, product name: P25, average primary particle diameter: 25 nm) was used as particle 1, and 540 mg of sea sand without through holes or pores (manufactured by Kishida Chemical, particle size: 370 to 840 μm) was used as particle 2.
[0167] For the quartz tubes equipped with the packed layers obtained in Examples 8 to 10 and Comparative Example 6, a gas flow test was carried out in the same manner as in Comparative Example 1. However, argon gas was used instead of helium gas, and the pressure was measured when the argon gas flow rate was 100 mL / min. The measurement was repeated until no change in pressure loss was observed.
[0168] The relationships between particle 1, particle 2, and the packed layer in Examples 8 to 10 and Comparative Example 6 are shown in Table 4. In addition, for Examples 8 to 10 and Comparative Example 6, the bulk density of particle 1, the bulk density of particle 2, and the bulk density of the packed layer were calculated from the above-mentioned formula, and the results are shown in Table 4.
[0169] [Table 4]
[0170] In Examples 8 to 10 and Comparative Example 6, before each test, the blue color of the titanium oxide fine particles colored with brilliant blue was uniformly dispersed in the packed bed. After the tests of Examples 8 to 10, the entire column was uniformly blue, confirming the suppression of the outflow of titanium oxide fine powder. On the other hand, after the test of Comparative Example 6, the blue color on the inlet side of the column disappeared and became lighter, and blue fine particles were deposited on the outlet side, so that it was visually confirmed that the titanium oxide fine powder had moved due to the flow of argon gas. Furthermore, in Comparative Example 6, the pressure loss normalized to 10 mm increased from the initial value of 19 kPa to 167 kPa after 10 minutes of continuous measurement due to the gas flow, and it is considered that the pressure loss increased due to clogging on the outlet side while the fine powder was outflowing. In other words, after the test of Comparative Example 6, it was confirmed that the outflow of titanium oxide fine powder could not be suppressed.
[0171] An example of an optical resolution column using the packed bed of the present invention will be described below. Specifically, an example of a catalyst column for dynamic optical resolution of racemized alcohol will be described.
[0172] In this dynamic optical resolution method, when a solution containing racemic alcohol is passed through a column packed with a solid phase containing a mixture of vanadium oxide-immobilized mesoporous silica nanoparticles (V-MPS4) and the hydrolytic enzyme lipase (e.g., CAL-B), the R- or S-enantiomer of the racemic alcohol is eluted from the column outlet. The reaction mechanism is that one optical isomer of the racemic alcohol is selectively esterified by optical resolution using lipase, while the other optical isomer of the racemic alcohol is racemized by the vanadium oxide contained in V-MPS4. These two reactions proceed simultaneously, converting all of the racemic alcohol into one optically active ester.
[0173] When V-MPS4 and CAL-B are mixed with particles (gap filling material) such as celite or silica gel and packed into a column, the particle diameters of V-MPS4 and CAL-B are different, so the fine particles of V-MPS4, which have a smaller particle diameter, move to the outlet side with the fluid. This causes a problem that the initial state in which the two types of catalysts are uniformly distributed is lost and the catalytic activity cannot be stably demonstrated. Therefore, this problem was solved by mixing silica porous particles as a gap filling material to fix these two types of catalyst particles inside the column.
[0174] Hereinafter, Particle 1 (V-MPS4) corresponds to the fine powder of the present invention, Particle 2 plays a role as a gap filler, and lipase (CAL-B) plays a role as an enzyme. Note that Particle 2 (silica porous particles) used in Examples 11 to 25 corresponds to the porous particles of the present invention.
[0175] Example 11 20 mg of V-MPS4 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., average primary particle size 1 μm, pore size 4 nm, vanadium content 0.2 mmol / g) as particle 1, 140 mg of silica porous particles (manufactured by SNG Corporation, lot number: PM043, most frequent pore size distribution of through holes: 2 μm, most frequent pore size distribution of pores: 6 nm, particle size: 20 to 63 μm) as particle 2, and 300 mg of CAL-B (Candida antarctica lipase B, manufactured by Roche, particle size: 300 to 700 μm) as lipase were placed in a glass container. Then, under an inert gas argon atmosphere, the mixture was shaken well by hand to obtain a mixture of particle 1, particle 2, and lipase.
[0176] Next, the mixture was poured into an Omnifit EZ empty column (Isis Co., Ltd., inner diameter 6.6 mm) using a medicine spoon, and uniformly distributed to obtain a packed bed. After that, the packed bed was compressed and fixed by tightening the movable plug of the Omnifit EZ empty column without tapping, and a column for catalytic reaction was prepared. The column was placed in a thermostatic device at 35°C. Next, raw material compound (1a) and an acetonitrile solution containing 4 molar equivalents of vinyl acetate relative to raw material compound (1a) (concentration of 1a: 0.1 M) were fed into the prepared column for catalytic reaction at a flow rate of 0.03 mL / min. After 3 hours of continuous pumping, the raw material compound (1a), the target compound (1b) and the by-product (1c) present in the solution obtained from the outlet of the column were analyzed by 1H-NMR and HPLC, and the yield (%) and optical purity (%ee) of the raw material compound (1a) and the target compound (1b), as well as the yield (%) of the by-product (1c) were calculated. The by-product (1c) was a dimer ether of the raw material compound (1a).
[0177] The structural formula of the starting compound (1a) is as follows. [ka]
[0178] The structural formula of the target compound (1b) is as follows. [ka]
[0179] Comparative Example 7 The test was performed in the same manner as in Example 11, except that 280 mg of single-pore silica gel particles (manufactured by Kanto Chemical Co., Ltd., particle size: 40 to 50 μm, pores: 6 nm) having no through-holes but having fine pores were used as particles 2.
[0180] Comparative Example 8 The same test as in Example 11 was performed except that 500 mg of Celite particles (manufactured by Kishida Chemical Co., Ltd., particle size: 20 to 100 μm) having neither through holes nor fine pores was used as the particles 2.
[0181] The results of Example 11 and Comparative Examples 7 and 8 are shown in Table 5 below.
[0182] [Table 5]
[0183] As shown in Table 5, in Example 11, 96% of the raw material compound (1a) was reacted (= reaction rate 96%), and the target compound (1b) was produced in a yield of 87% and with an optical purity of 98%ee. The reaction rate in Example 11 was higher than that in Comparative Example 7 (= reaction rate 78%) and Comparative Example 8 (= reaction rate 72%). This leads to the target compound (1b) being given in a high yield even under the same reaction conditions. In addition, the optical purity of the raw material compound (1a) recovered in Example 11 was lower than that in Comparative Examples 7 to 8, indicating that racemization proceeded rapidly in the case of Example 11. This is an extremely important result in terms of efficiently performing dynamic optical resolution. Furthermore, in Example 11, although the weight of the particle 2 (gap filling material) was less than half that of Comparative Examples 7 and 8, dynamic optical resolution with high efficiency, high yield, and high optical purity was possible.
[0184] In Example 11 and Comparative Examples 7 to 8, the beige color of V-MPS4 was uniformly dispersed in the packed bed before each test. After the test in Example 11, the entire column was uniformly beige, confirming that the movement of V-MPS4, which is a fine powder, could be suppressed. On the other hand, after the tests in Comparative Examples 7 to 8, the beige color on the inlet side of the column disappeared and became white, and the beige color on the outlet side became darker, confirming with the naked eye that the fine powder V-MPS4 had moved due to the liquid delivery. In other words, after the tests in Comparative Examples 7 to 8, it was confirmed that the movement of V-MPS4, which is a fine powder, could not be suppressed.
[0185] Hereinafter, the starting compound (1a), the target compound (1b) and the by-product (1c) in Examples 12 to 19 are the same as the starting compound (1a), the target compound (1b) and the by-product (1c) in Example 11.
[0186] Example 12 A catalytic reaction column was prepared under the same conditions as in Example 11, except that 61 mg of V-MPS4 was used as particle 1 and 118 mg of silica porous particles were used as particle 2, and the column was placed in a thermostatic device at 35°C. Then, raw material compound (1a) and an acetonitrile solution containing 4 molar equivalents of vinyl acetate relative to raw material compound (1a) (concentration of 1a: 0.1M) were fed to the prepared catalytic reaction column at a flow rate of 0.03mL / min. After continuous feeding for 3 hours, raw material compound (1a), target compound (1b) and by-product (1c) present in the solution obtained from the column outlet were analyzed by 1H-NMR and HPLC, and the yield (%) and optical purity (%ee) of raw material compound (1a) and target compound (1b), as well as the yield (%) of by-product (1c) were calculated.
[0187] Example 13 A column for catalytic reaction was prepared under the same conditions as in Example 11, except that 30 mg of V-MPS4 was used as particle 1 and 135 mg of porous silica particles were used as particle 2, and the column was placed in a thermostatic device at 35° C. Then, a test was performed under the same conditions as in Example 12, and the yield (%) and optical purity (% ee) of the raw material compound (1a), the target compound (1b), and the by-product (1c), as well as the yield (%) of the by-product (1c), were calculated.
[0188] Example 14 A column for catalytic reaction was prepared under the same conditions as in Example 11, except that 15 mg of V-MPS4 was used as particle 1 and 140 mg of porous silica particles was used as particle 2, and the column was placed in a thermostatic device at 35° C. Then, a test was performed under the same conditions as in Example 12, and the yield (%) and optical purity (% ee) of the raw material compound (1a), the target compound (1b), and the by-product (1c), as well as the yield (%) of the by-product (1c), were calculated.
[0189] Example 15 61 mg of V-MPS4 was used as particle 1, and 118 mg of silica porous particles were used as particle 2. The packed bed was divided into a first region, a second region, and a third region from the upstream side to the downstream side in the flow direction of the liquid in the packed bed, and the mixing ratio (weight ratio) of particle 1 to particle 2 in each region was set to first region = 1: 4.1, second region = 1: 2.4, third region = 1: 1, and the mixing ratio (weight ratio) of particle 1 to lipase was set to first region = 1: 9.1, second region = 1: 5.9, third region = 1: 3.03. A column for catalytic reaction was prepared under the same conditions as in Example 11, and the column was placed in a thermostatic device at 35 ° C. Subsequently, a test was performed under the same conditions as in Example 12, and the yield (%) and optical purity (% ee) of the raw material compound (1a), the target compound (1b), and the by-product (1c), as well as the yield (%) of the by-product (1c) were calculated. The lengths of the first, second and third regions are the lengths of the packed bed divided into three equal parts. That is, the length of the packed bed is the sum of the length of the first, second and third regions. The same applies to the following Examples 16 to 19.
[0190] Example 16 30 mg of V-MPS4 was used as particle 1, and 135 mg of silica porous particles were used as particle 2. The mixing ratio (weight ratio) of particle 1 to particle 2 in each region was 1:7.8 in the first region, 1:4.5 in the second region, and 1:3.1 in the third region, and the mixing ratio (weight ratio) of particle 1 to lipase was 1:16.7 in the first region, 1:10 in the second region, and 1:7.1 in the third region. Except for this, a column for catalytic reaction was prepared under the same conditions as in Example 11, and the column was placed in a thermostatic device at 35°C. Subsequently, a test was performed under the same conditions as in Example 12, and the yield (%) and optical purity (%ee) of the raw material compound (1a), the target compound (1b), and the by-product (1c), as well as the yield (%) of the by-product (1c) were calculated.
[0191] (Example 17) 22 mg of V-MPS4 was used as particle 1, and 139 mg of silica porous particles were used as particle 2. The mixing ratio (weight ratio) of particle 1 to particle 2 in each region was 1:9.6 in the first region, 1:6.6 in the second region, and 1:4.5 in the third region, and the mixing ratio (weight ratio) of particle 1 to lipase was 1:20 in the first region, 1:14.3 in the second region, and 1:10 in the third region. Except for this, a column for catalytic reaction was prepared under the same conditions as in Example 11, and the column was placed in a thermostatic device at 35°C. Subsequently, a test was performed under the same conditions as in Example 12, and the yield (%) and optical purity (%ee) of the raw material compound (1a), the target compound (1b), and the by-product (1c), as well as the yield (%) of the by-product (1c) were calculated.
[0192] (Example 18) A column for catalytic reaction was prepared under the same conditions as in Example 11, except that 15 mg of V-MPS4 was used as particle 1, and 143 mg of silica porous particles were used as particle 2, and the ratio of particle 1 to particle 2 was changed by dividing the packed bed into a first region, a second region, and a third region from the upstream side to the downstream side in the flow direction of the liquid in the packed bed. The mixing ratio (weight ratio) of particle 1 to particle 2 in each region was 1:16.3 for the first region, 1:9.6 for the second region, and 1:6.6 for the third region, and the mixing ratio (weight ratio) of particle 1 to lipase was 1:33.3 for the first region, 1:20 for the second region, and 1:14.3 for the third region. The column was then placed in a thermostatic device at 35°C. Subsequently, the test was carried out under the same conditions as in Example 12, and the yield (%) and optical purity (%ee) of the starting compound (1a), the target compound (1b) and the by-product (1c), as well as the yield (%) of the by-product (1c) were calculated.
[0193] (Example 19) 22 mg of V-MPS4 was used as particle 1, and 139 mg of silica porous particles were used as particle 2. The mixing ratio (weight ratio) of particle 1 to particle 2 in each region was 1:4.5 in the first region, 1:6.6 in the second region, and 1:9.6 in the third region, and the mixing ratio (weight ratio) of particle 1 to lipase was 1:10 in the first region, 1:14.3 in the second region, and 1:20 in the third region. Except for this, a column for catalytic reaction was prepared under the same conditions as in Example 11, and the column was placed in a thermostatic device at 35°C. Subsequently, a test was performed under the same conditions as in Example 12, and the yield (%) and optical purity (%ee) of the raw material compound (1a), the target compound (1b), and the by-product (1c), as well as the yield (%) of the by-product (1c) were calculated.
[0194] The results of Examples 12 to 19 are shown in Table 6 below.
[0195] [Table 6]
[0196] As shown in Table 6, in comparison with the case where the mixing ratio of particle 1 and particle 2 was not changed from the upstream side to the downstream side, i.e., the mixing ratio of particle 1 and lipase was not changed (Examples 12 to 14), in the case where the mixing ratio of particle 1 and particle 2 was changed by dividing into the first region, the second region, and the third region, i.e., the mixing ratio of particle 1 and lipase was changed (Examples 15 to 18), the yield of by-product (1c) was reduced and the yield of target compound (1b) was improved. In all of Examples 15 to 18, the optical purity of target compound (1b) was 97% ee or more. In addition, in Examples 15 to 18, in which the weight of particle 1 was increased in the order of the first region, the second region, and the third region, and the weight of particle 2 was decreased, while the weight of lipase was kept constant, the yield of by-product (1c) was reduced and the yield of target compound (1b) was improved more than in Example 19, in which the weight of particle 1 was decreased in the order of the first region, the second region, and the third region, and the weight of particle 2 was increased.
[0197] (Example 20) A column for catalytic reaction was prepared under the same conditions as in Example 11, except that 100 mg of V-MPS4 was used as particle 1, and 98 mg of silica porous particles were used as particle 2, and the mixture ratio of particle 1 to particle 2 was changed by dividing the packed bed into a first region, a second region, and a third region from the upstream side to the downstream side in the flow direction of the liquid in the packed bed. The mixture ratio (weight ratio) of particle 1 to particle 2 in each region was 1:2.4 in the first region, 1:1 in the second region, and 1:0.5 in the third region, and the mixture ratio (weight ratio) of particle 1 to lipase was 1:5.9 in the first region, 1:3.03 in the second region, and 1:2 in the third region. The column was then placed in a thermostatic device at 35°C. Next, the raw material compound (2a) and an acetonitrile solution containing 4 molar equivalents of vinyl acetate relative to the raw material compound (2a) (concentration of 2a: 0.1M) were pumped into the prepared catalytic reaction column at a flow rate of 0.03mL / min. After 3 hours of continuous pumping, the raw material compound (2a), the target compound (2b) and the by-product (2c) present in the solution obtained from the column outlet were analyzed by 1H-NMR and HPLC, and the yield (%) and optical purity (%ee) of the raw material compound (2a) and the target compound (2b), as well as the yield (%) of the by-product (2c) were calculated. The by-product (2c) was a dimer ether of the raw material compound (2a).
[0198] The structural formula of the starting compound (2a) is as follows. [ka]
[0199] The structural formula of the target compound (2b) is as follows: [ka]
[0200] Example 21 A column for catalytic reaction was prepared under the same conditions as in Example 11, except that 43 mg of V-MPS4 was used as particle 1 and 129 mg of silica porous particles were used as particle 2, and the mixture ratio of particle 1 to particle 2 was changed by dividing the packed bed into a first region, a second region, and a third region from the upstream side to the downstream side in the flow direction of the liquid in the packed bed. The mixture ratio (weight ratio) of particle 1 to particle 2 in each region was 1:6.7 in the first region, 1:3.1 in the second region, and 1:1.8 in the third region, and the mixture ratio (weight ratio) of particle 1 to lipase was 1:14.3 in the first region, 1:7.1 in the second region, and 1:4.5 in the third region. The column was then placed in a thermostatic device at 35°C. Next, the raw material compound (3a) and an acetonitrile solution containing 4 molar equivalents of vinyl acetate relative to the raw material compound (3a) (concentration of 3a: 0.1M) were pumped into the prepared catalytic reaction column at a flow rate of 0.03mL / min. After 3 hours of continuous pumping, the raw material compound (3a), the target compound (3b) and the by-product (3c) present in the solution obtained from the column outlet were analyzed by 1H-NMR and HPLC, and the yield (%) and optical purity (%ee) of the raw material compound (3a) and the target compound (3b), as well as the yield (%) of the by-product (3c) were calculated. The by-product (3c) was a dimer ether of the raw material compound (3a).
[0201] The structural formula of the starting compound (3a) is as follows. [ka]
[0202] The structural formula of the target compound (3b) is as follows: [ka]
[0203] Example 22 A column for catalytic reaction was prepared under the same conditions as in Example 21, and the column was placed in a thermostatic device at 35°C. Then, the raw material compound (4a) and an acetonitrile solution containing 4 molar equivalents of vinyl acetate relative to the raw material compound (4a) (concentration of 4a: 0.1M) were fed to the prepared column for catalytic reaction at a flow rate of 0.03mL / min. After continuous feeding for 3 hours, the raw material compound (4a), the target compound (4b) and the by-product (4c) present in the solution obtained from the column outlet were analyzed by 1H-NMR and HPLC, and the yield (%) and optical purity (%ee) of the raw material compound (4a) and the target compound (4b), as well as the yield (%) of the by-product (4c) were calculated. The by-product (4c) was a dimer ether of the raw material compound (4a).
[0204] The structural formula of the starting compound (4a) is as follows. [ka]
[0205] The structural formula of the target compound (4b) is as follows: [ka]
[0206] (Example 23) A column for catalytic reaction was prepared under the same conditions as in Example 21, and the column was placed in a thermostatic device at 35°C. Then, the raw material compound (5a) and an acetonitrile solution containing 4 molar equivalents of vinyl acetate relative to the raw material compound (5a) (concentration of 5a: 0.1M) were fed to the prepared column for catalytic reaction at a flow rate of 0.015mL / min. After continuous feeding for 6 hours, the raw material compound (5a), the target compound (5b), and the by-product (5c) present in the solution obtained from the column outlet were analyzed by 1H-NMR and HPLC, and the yield (%) and optical purity (%ee) of the raw material compound (5a) and the target compound (5b), as well as the yield (%) of the by-product (5c) were calculated. The by-product (5c) was a dimer ether of the raw material compound (5a).
[0207] The structural formula of the starting compound (5a) is as follows. [ka]
[0208] The structural formula of the target compound (5b) is as follows: [ka]
[0209] Example 24 A column for catalytic reaction was prepared under the same conditions as in Example 11, except that 150 mg of V-MPS4 was used as particle 1, and 75 mg of silica porous particles were used as particle 2, and the mixture ratio of particle 1 to particle 2 was changed by dividing the packed bed into a first region, a second region, and a third region from the upstream side to the downstream side in the flow direction of the liquid in the packed bed. The mixture ratio (weight ratio) of particle 1 to particle 2 in each region was 1:1 for the first region, 1:0.5 for the second region, and 1:0.25 for the third region, and the mixture ratio (weight ratio) of particle 1 to lipase was 1:3.03 for the first region, 1:2 for the second region, and 1:1.49 for the third region. The column was then placed in a thermostatic device at 35°C. Next, the raw material compound (6a) and an acetonitrile solution containing 4 molar equivalents of vinyl butyrate relative to the raw material compound (6a) (concentration of 6a: 0.1M) were pumped into the prepared catalytic reaction column at a flow rate of 0.03mL / min. After 3 hours of continuous pumping, the raw material compound (6a), the target compound (6b) and the by-product (6c) present in the solution obtained from the column outlet were analyzed by 1H-NMR and HPLC, and the yield (%) and optical purity (%ee) of the raw material compound (6a) and the target compound (6b), as well as the yield (%) of the by-product (6c) were calculated. The by-product (6c) was a dimer ether of the raw material compound (6a).
[0210] The structural formula of the starting compound (6a) is as follows. [ka]
[0211] The structural formula of the target compound (6b) is as follows: [ka]
[0212] The results of Examples 16 and 20 to 24 are shown in Table 7 below.
[0213] [Table 7]
[0214] In Examples 20 to 24, similar to Example 11, each target compound was obtained in a yield of 90% or more and with an optical purity of 96% ee or more, demonstrating that dynamic optical resolution proceeds smoothly even for a wide range of compounds with different substituents.
[0215] Hereinafter, the starting compound (2a), the target compound (2b) and the by-product (2c) in Example 25 are the same as the starting compound (2a), the target compound (2b) and the by-product (2c) in Example 20.
[0216] (Example 25) A catalytic reaction column was prepared under the same conditions as in Example 11, except that 100 mg of V-MPS4 was used as particle 1, 100 mg of silica porous particles as particle 2, and 300 mg of CAL-B was used as lipase, and the column was placed in a thermostatic device at 35°C. Then, raw material compound (2a) and an acetonitrile solution containing 4 molar equivalents of vinyl acetate relative to raw material compound (2a) (concentration of 2a: 0.1M) were fed to the prepared catalytic reaction column at a flow rate of 0.03mL / min. After every 6 hours of continuous feeding, the solution obtained from the column outlet was collected, and continuous feeding was performed for a total of 78 hours. The raw material compound (2a), target compound (2b), and by-product (2c) present in each solution obtained from the column outlet were analyzed by 1H-NMR and HPLC, and the yield (%) and optical purity (%ee) of raw material compound (2a) and target compound (2b), as well as the yield (%) of by-product (2c) were calculated.
[0217] The results of Example 25 are shown in Table 8 below.
[0218] [Table 8]
[0219] From the results of Example 25, even after continuous liquid transfer for 78 hours, the yield of the target product (2b) was stable at around 90%, and the optical purity did not decrease at 99% ee, indicating that the catalyst can be used continuously without deterioration.
Claims
1. A packed bed formed of a mixture of porous particles and fine powder, (1) The porous particle has a skeleton, the skeleton has through holes, the through holes have a diameter of 0.1 to 100 μm, the through holes have a most frequent pore size of 0.5 μm or more and 50 μm or less in a pore size distribution, and the porous particle has a particle size of 20 μm or more and 3000 μm or less, (2) the average primary particle size of the fine powder is 1 nm or more and is 80% or less of the most frequent pore size in the pore size distribution of the through holes; (3) The bulk density of the porous particles is 0.05 to 7.5 (mg / mm 3 ) A packed bed characterized by:
2. The bulk density of the fine powder is 0.02 to 7.5 (mg / mm 3 2. The filling bed according to claim 1 ,
3. The bulk density of the packed bed is 0.05 to 7.5 (mg / mm 3 3. The filling bed according to claim 1 or 2, wherein
4. The filling bed according to any one of claims 1 to 3, A packed bed, in which a mixing ratio of the porous particles and the fine powder in the packed bed changes stepwise.
5. The packed bed according to any one of claims 1 to 4, wherein the mixture further comprises enzyme particles.
6. 6. The packed bed of claim 5, wherein the enzyme particles are lipase.
7. The packed bed according to claim 5 or 6, A packed bed, in which a mixing ratio of the fine powder and the enzyme particles in the packed bed changes stepwise.
8. A method for passing a gas or liquid through a pipe provided with the packed bed according to any one of claims 1 to 7.
Citation Information
Patent Citations
Method for manufacturing catalyst
JP2006506224A
Catalyst using palladium-ruthenium composite fine particle, and method of producing the same
JP2019030827A